Penerapan Paradigma Whole Of Government dalam Pelayanan Pusat Pembelajaran Keluarga pada Kelurahan Pakis, Kecamatan Sawahan, Kota Surabaya - Alimi, Fadllal; Arundinasari, Indira (VISA: Journal of Vision and Ideas, 2024)
This study aims to reveal the form of the Whole of Government paradigm in the implementation of the PUSPAGA Balai RW program in Surabaya City. The policy implementation review uses Edward III's policy implementation factor analysis, which states the success of policy implementation on four factors, namely communication, resources, disposition, and bureaucratic structure. The research location is in RW 03, Pakis, Sawahan District, Surabaya City. The research used a qualitative approach with a descriptive method. The research data uses secondary data and primary data. Secondary data collection techniques use literature study techniques. Primary data collection uses two methods, namely observation and interview. The observations were conducted for four months from September to December. Interviews were conducted with two informants, namely Kasie Kesra, Village, and Surabaya RW 3 Cadre Coordinator Village. The results revealed that the four factors of Edward III's policy implementation had been well implemented. The Puspaga policy implementation process involves various stakeholders to achieve program success. The Puspaga program in RW 3 Village, has a positive impact on community welfare because it reduces the number of Domestic Violence. Based on this description, it was concluded that the Puspaga program is an application of the Whole of Government Paradigm.